1964
DOI: 10.2135/cropsci1964.0011183x000400060032x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Behavior and Histological Structure of a Nondehiscent Anther Character in Sorghum vulgare Pers.1

Abstract: T HIS paper reports the breeding behavior of a nondehiscent anther character which first appeared in a cross involving an African sorghum variety. Anatomical and histological differences between normal and nondehiscent anthers are also presented. MATERIALS AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…It therefore, appears that the persistence of tapetal cells is not necessarily associated with male sterility and, therefore, some abnormality other than the tapetal degenera tion also exists in some A-lines leading to the male sterility. However, these investi gations and similar studies undertaken by previous researchers (Fillion andChristie 1966, Webster andSingh 1964) suggest that endothecium also play a major role in as much as all the pollen fertile lines possessed very thin endothecium compared to very thick endothecium in A-lines (Figs. 1 and 2).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…It therefore, appears that the persistence of tapetal cells is not necessarily associated with male sterility and, therefore, some abnormality other than the tapetal degenera tion also exists in some A-lines leading to the male sterility. However, these investi gations and similar studies undertaken by previous researchers (Fillion andChristie 1966, Webster andSingh 1964) suggest that endothecium also play a major role in as much as all the pollen fertile lines possessed very thin endothecium compared to very thick endothecium in A-lines (Figs. 1 and 2).…”
Section: Methodssupporting
confidence: 86%
“…In A-lines the situation was reverse in that it was thinner at stage-I but rapidly increased in thickness towards maturation (Table 1). The increase in thickness of endothecium has contributed to the non-dehiscence of anthers in A-lines as was observed in orchard grass (Fillion and Christie 1966) and sorhgum (Webster and Singh 1964).…”
Section: Methodsmentioning
confidence: 75%
“…A second type of cytoplasmic male sterility is caused by non dehiscence of anthers and has been developed from progenies of crosses of the Martin line with an African Sorghum variety 9E [23]. In this case fertility can be restored by nuclear genes carried in the Feterita varieties but not by Milo [23] indicating that the cytoplasm of 9E is probably different from that of Milo.…”
Section: Introductionmentioning
confidence: 99%
“…Differences have also been reported in endothecial development in male fertile and male sterile strains (Pritchard and Hutton, 1972) and it was shown that thick endothecium gradually becomes attenuated to facilitate dehiscence in male fertile sorghum (Webster and Singh 1964), orchard grass (Fillion and Christie 1966) and pearl millet (Reddy andReddi 1970, 1974). In sterile material no such phenomenon was obterved.…”
Section: Discussionmentioning
confidence: 94%